Investment Horizon to Investment Decision and Mean Reversion: Indonesian Perspective - Eddy Junarsin; Eduardus Tandelilin (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This study has two research objectives: (1) to find evidence whether investment decisions (allocation of funds in each asset in a portfolio) of Indonesian investors in the short investment horizon diverge with their investment decisions in the long investment horizon, and (2) to examine the belief of Indonesian investors in the mean reversion. This study analyzes the investment horizon from a behavioral point of view by examining the influence of investment horizon on investment decision and mean reversion in Indonesia. We employed the students of Master of Science, Master of Management, and Doctorate Programs at the Faculty of Economics and Business, Universitas Gadjah Mada, Indonesia as the sample in this research. Of the 217 questionnaires delivered, 172 questionnaires were completely filled and utilized in this study.The main findings of this study are as follows: (1) it is significantly proved that Indonesian investors are inclined to assume higher portfolio risk in the longer investment horizon than that in the shorter investment horizon; (2) it is very interesting to see that on average, the investors are inclined to increase their allocation in the risk-free asset in the longer investment horizon although the difference between the risk-free asset holding in the short investment horizon and that in the long investment horizon is not significant; (3) the framing effect significantly influences the investment decisions, both in short investment horizon and in long investment horizon; (4) there is a tendency for the respondents to show a willingness to assume higher portfolio risk when they received the questionnaires that provided the historical five-year returns on the first page; (5) investors predict an asset gaining 50 percent in the first year to continuously gain in the next four years while expecting an asset losing 25 percent in the first year to continuously loss in the next four years.